THE ROLE OF INSTITUTIONS AND GLOBALIZATION TOWARDS INCLUSIVE AND SUSTAINABLE GREEN DEVELOPMENT (INCLUSIVE GREEN GROWTH) - Sudarsana Arka; Ni Putu Pramitha Purwanti; I Wayan Wenagama (Jurnal Ekonomi Kuantitatif Terapan, 2024)
The idea of a green economy does not replace sustainable development, but creates a new focus on the economy,investment, capital and infrastructure, jobs and skills as well as positive social and environmental outcomes. Thegreen economy is closely related to SDGs No. 13, climate action, but, even further, this concept directs attention tothe quality of life with people at the center. This research tries to see the impact of the development of inclusive greengrowth in several countries on the welfare of their people. Inclusive green growth prioritizes planetary and humanhealth, and considers them interrelated. Prioritization and implementation of green initiatives also helps countriesachieve various sustainable development goals. The hypothesis tested is that countries that implement inclusivegreen growth in their development policies will have a strong correlation with community welfare, governance ofgovernment institutions, and economic openness in the context of international trade. The results of data analysisshow that inclusive green growth has a positive and insignificant effect on economic openness in various countries.Government institutional governance has a positive and insignificant effect on economic openness in variouscountries. Inclusive green growth has a positive and significant effect on the welfare of society in various countries.The governance of government institutions has a negative and insignificant effect on the welfare of society invarious countries. Economic openness has a positive and significant effect on the welfare of society in variouscountries. Inclusive green growth does not have an indirect effect on the welfare of society in various countries. Thegovernance of government institutions does not indirectly influence the welfare of society in various countries.